1995
DOI: 10.1006/viro.1995.0027
|View full text |Cite
|
Sign up to set email alerts
|

Murine Leukemia Virus-Induced Neurodegeneration of Rats: Enhancement of Neuropathogenicity Correlates with Enhanced Viral Tropism for Macrophages, Microglia, and Brain Vascular Cells

Abstract: A highly neuropathogenic retrovirus, NT40, was generated by serially passaging an infectious molecular clone of Friend murine leukemia virus, FB29, through F344 Fisher rats. NT40 induced severe neurological signs such as reflex abnormalities and ataxia within 4-6 weeks following neonatal inoculation. FB29 led to only very mild neurological dysfunctions with longer incubation periods. Pathological alterations were characterized by mild (FB29) to extensive (NT40) noninflammatory spongiform degeneration, mainly o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
24
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…In rodents, some of the murine leukemia viruses (MuLV) cause a nonin¯ammatory neurodegeneration, restricted to selective areas of the central nervous system (CNS) and the spinal cord (Baszler and Zachary, 1990;Czub et al, 1994Czub et al, , 1995Kay et al, 1991). Most neurovirulent MuLV as well as certain lentiviruses including the human, simian, and feline immunode®ciency viruses (HIV, SIV, FIV) exhibit a strong af®nity for cells of the monocytic lineage, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rodents, some of the murine leukemia viruses (MuLV) cause a nonin¯ammatory neurodegeneration, restricted to selective areas of the central nervous system (CNS) and the spinal cord (Baszler and Zachary, 1990;Czub et al, 1994Czub et al, , 1995Kay et al, 1991). Most neurovirulent MuLV as well as certain lentiviruses including the human, simian, and feline immunode®ciency viruses (HIV, SIV, FIV) exhibit a strong af®nity for cells of the monocytic lineage, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Most neurovirulent MuLV as well as certain lentiviruses including the human, simian, and feline immunode®ciency viruses (HIV, SIV, FIV) exhibit a strong af®nity for cells of the monocytic lineage, i.e. in the CNS these viruses infect primarily microglia cells (Brinkmann et al, 1992;Czub et al, 1995Czub et al, , 1996Lynch et al, 1991). However, while infected microglia cells appear not to be morphologically altered, degenerating neurons do not express retroviral gene products (Baszler and Zachary, 1990;Czub et al, 1994Czub et al, , 1995Kay et al, 1991;Koenig et al, 1986;Lynch et al, 1991;Wiley et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery of CasBrE MLV 20 years ago, other neuropathogenic murine retroviruses have been found. In the ecotropic host range group, variants of Friend MLV, including PVC211 [10], NT40 [4], A8 [25], and PVC441 [27] , and temperature sensitive-mutants of Moloney MLV, including ts1 [30,31] and ts-BA1 [2], cause neurodegenerative disease in mice and/or rats. The neuropathology of these viruses is characterized by spongiform neurodegeneration without inflammatory infiltrates, primarily involving the motor system of the brain and spinal cord, and is associated with widespread astrogliosis and neuropil vacuolation [1,3,17,24].…”
mentioning
confidence: 99%
“…As shown in Fig. 1, after administration of [1-13 C] glucose into the animals, the [1-13 C] glucose incorporated into brain cells is converted to [3][4][5][6][7][8][9][10][11][12][13] C] pyruvate and non-labeled pyruvate by glycolysis. This pyruvate is converted to acetylCoA through the pyruvate dehydrogenase complex and then enters the citric acid cycle.…”
mentioning
confidence: 99%
“…
Friend murine leukemia virus (FrMLV) clone A8 causes a progressive neurodegenerative disease when the virus is inoculated into newborn rats in addition to the related clones PVC211 and FB29, and of a variant, NT40, derived from FB29 (5,16,24). It has been reported that PVC211, FB29 and NT40 do not induce leukemia in rats, as they do in mice (16,17,23,25).
…”
mentioning
confidence: 99%